Methodological strategies to improve the reading comprehension of fourth grade students - Arias Duque, Luis Armando; Pardo Quiroz, Kelly Pamela; Sáenz Rodríguez, Janina Susana; Rodríguez Romero, Shirley Giomar (Revista Universidad de Guayaquil, 2022)
Degree work has the title: Methodological strategies for reading comprehension of students in the 4th. Year Basic Education Learning Center “ Cristóbal Colón” Cantón of Guayaquil in the 2014-2015 school year this research work aims to develop new methodological strategies for reading comprehension, how to achieve is through a practical guide of recreational reading to improve reading comprehension, whose proposal is justified in order to encourage students to communicate, interpret ideas and that you understand them and then give its assessment of a given subject, making it necessary to indicate that the methodological strategies are responsible for establishing what is needed to resolve well the task of study, determine the most appropriate techniques to be used, monitor its implementation and subsequent decisions are made based on the results, and the reading comprehension is a process through which the reader produces a meaning in their interaction with the text. The methodology used were the methods: empirical, scientific, deductive, inductive, analytic- synthetic, using survey techniques, interviews, obtaining the following data that teachers do not use methodological strategies, sometimes there is time for activities creativity and reading comprehension exercises, while students are not critics like to read because they are not motivated and representatives say they need help to make reading comprehension, it is therefore necessary to apply methodological strategies with to improve reading, whose impact will be of great benefit to the development of vocabulary and reading habits form.
Keywords: Reading comprehension; Methodology